2017
DOI: 10.3102/0002831217729875
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates High School Students to Want to Be Teachers? The Role of Salary, Working Conditions, and Societal Evaluations About Occupations in a Comparative Perspective

Abstract: This study examines between-country differences in the degree to which teachers’ working conditions, salaries, and societal evaluations about desirable job characteristics are associated with students’ teaching career expectations. Three-level hierarchical generalized linear models are employed to analyze cross-national data from the Programme for International Student Assessment (PISA). Results reveal that teacher salaries and societal evaluations about the importance of job responsibility and respect are pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 51 publications
5
44
0
1
Order By: Relevance
“…Teacher Salary Most teacher retention and recruitment studies have indicated that teacher compensation is an important issue [19]. In this sample, very few individuals thought teachers are well paid for what they do.…”
Section: Analysis Of Other Influential Factors Predicting Students' Dmentioning
confidence: 86%
See 1 more Smart Citation
“…Teacher Salary Most teacher retention and recruitment studies have indicated that teacher compensation is an important issue [19]. In this sample, very few individuals thought teachers are well paid for what they do.…”
Section: Analysis Of Other Influential Factors Predicting Students' Dmentioning
confidence: 86%
“…Research has also shown that pay and work conditions have been identified as factors that dissuade individuals from becoming teachers [18]. Many of those choosing to teach have been able to overlook some negative aspects like low pay and difficult work conditions because they considered teaching to be a calling, citing altruistic or social utility motivations [16,19]. Factors that researchers have identified as impacting whether or not an individual will enter the teaching profession are presented in Table 1.…”
Section: Review Of Factors Influencing Teacher Recruitment Literaturementioning
confidence: 99%
“…But at the same time, there are differences in the level of dependence between conditions for science education teachers. Thus, the relationship between salary and career expectations, assessments in society and career expectations differs among students with different levels of subject knowledge (Han et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has indicated that extrinsic motivations for choosing teaching as a career are status of the profession, levels of pay, benefits, holidays and vacation time, job security, and time compatibility (Lortie, 1975;Heinz 2015). Research also suggests college aged individuals tend to choose teaching as a career more readily for intrinsic and altruistic reasons while high school students are motivated more by extrinsic factors such as salary and job conditions (Han et al, 2018). In agricultural education, literature suggests barriers to entrance into the agriculture teaching profession are extrinsic motivators such as family responsibilities and relationships, desire to live in a certain area, and unwillingness to move away (Rocca & Washburn, 2008).…”
Section: Valuesmentioning
confidence: 99%